Working with LGBTQIA+ youth in the child welfare system Perspectives from youth and professionals - López López, Mónica; González Álvarez, Rodrigo; ten Brummelaar, Mijntje; van Mierlo, Kevin; Wieldraaijer-Vincent, Leo (University of Groningen Press, 2021)
Written through a constant exchange between LGBTQIA+ young people, researchers, professionals and foster families, this book offers a valuable tool to improve the practice with LGBTQIA+ youth at a personal, organizational, and policy level. This book shows the powerful influence of relationships and networks for the LGBTQIA+ young person growing up in child protection and welfare systems. LGBTQIA+ youth need meaningful connections with individuals within their communities in order to be able to heal, learn, and be authentically themselves. Child welfare professionals have a crucial role in creating these connections and cultivating supportive environments, free of additional trauma, where LGBTQIA+ young people can feel valued and loved.